Development of LAMP assay for early detection of Yersinia ruckeri in aquaculture - Abbas, Hoda; Best, Nickala; Zerna, Gemma; Beddoe, Travis (PeerJ, 2025)
Yersinia ruckeri is the causative agent of yersiniosis or enteric red mouth disease (ERM) that causes significant economic losses in the salmonid aquaculture industry. Due to an increasing number of outbreaks, lack of effective vaccines and the bacteria’s ability to survive in the environment for long periods, there is a necessity for novel measures to control ERM. New techniques capable of rapidly detecting Y. ruckeri are critical to aid effective control programs. Molecular methods, like real-time polymerase chain reaction, can detect Y. ruckeri; however, that methodology is not field-deployable and cannot support local decision-making during an outbreak. We present a field-deployable molecular assay using loop mediated isothermal amplification (LAMP) and water filtering method for the detection of Y. ruckeri eDNA from water samples to improve current surveillance methods. The assay was optimised to amplify the glutamine synthetase gene (glnA) of Y. ruckeri in under 20 min. The assay demonstrated high specificity and sensitivity, as it did not amplify any non-target bacteria typically present in water sources. It achieved a limit of detection (LOD) of 0.5 × 10−7 ng/µl, significantly surpassing the LOD of 0.5 × 10−4 ng/µl obtained through conventional polymerase chain reaction (cPCR). When applied to environmental water samples spiked with transformed Escherichia coli containing the G-block of the Yersinia ruckeri (glnA) target gene, the Yr-LAMP method exhibited an analytical sensitivity of 0.08 cells/µl from the initial filtered water sample. Notably, the cumulative time for sample preparation and amplification was under 1 h. The simplicity of the developed field-deployable Yr-LAMP assay makes it suitable as a routine procedure to monitor fish for ERM infection. This will enable informed decision-making on mitigating pathogen prevalence in aquaculture farms.
Keywords: LAMP; Aquaculture; Yersinia ruckeri; Enteric red mouth disease; Point-of-care; Diagnostic; Yersiniosis